Effect of rice husk particle size on ZSM-5 physico-chemical properties for selective formation of 1,3,5-trimethyl-2-benzylbenzene (Pharmaceutical Intermediate) - Ghuge, Gorakh; Niphadkar, Prashant; Rathod, Simmy; Bokade, Vijay V. (ChemistrySelect, 2021)
Rice husk, rich in silica and abundantly available as waste, is presently destroyed by burning, which creates environmental issues. Thus, it will be advantageous if this rice husk waste can be used for preparation of valuable products. One of the application is its use as silica source in the synthesis of zeolites like ZSM-5, which are silico-aluminates. Rice husk waste is available in wide range of particle sizes in agricultural farms. There is no study available in open literature on use of these wide particle ranges for its direct application. This paper is an attempt to use wide particle size rice husk, its effect on ZSM-5 synthesis and its physico-chemical properties. Further these prepared ZSM-5 catalyst was evaluated for benzylation of mesitylene reaction. The study found that, rice husk of 600 mu m particle size is optimum as far as ZSM-5 synthesis, its physicochemical properties and further its application in mesitylene benzylation reaction.
Keywords: Mesitylene; Particle size; rice husk; Silica Source; ZSM-5

One-pot cascade conversion of renewable furfural to levulinic acid over a bifunctional H3PW12O40SiO2 catalyst in the absence of external H-2 - Nandiwale, Kakasaheb Y.; Vishwakarma, Mona; Rathod, Simmy; Simakova, Irina; Bokade, Vijay V. (Energy & Fuels, 2021)
The conversion of biomass-derived furfural (FUR) to levulinic acid (LA), a versatile platform chemical, involves catalytic hydrogenation of FUR followed by acid hydrolysis to LA. However, this two-step process demands expensive separation and purification of the furfuryl alcohol (FAL) intermediate. Herein, we demonstrate an ingenious catalytic strategy for the one-pot cascade conversion of FUR to LA over a bifunctional catalyst without using pure external H-2. Isopropyl alcohol (IPA) served a dual role as a hydrogen donor and solvent while inhibiting the side reactions. Catalysts with a tunable surface area and acidity were synthesized by impregnating different percentages of H3PW12O40 (heteropolyacid) over a SiO2 support. The bifunctionality of the H3PW12O40/SiO2 catalyst is ascribed to the mutual coexistence of Lewis and Brvinsted acid sites. The Lewis acid sites imparted by active W metal sites adsorb hydrogen proton for catalytic transfer hydrogenation of FUR to FAL, while the predominant Brvinsted acid sites catalyze the hydrolysis of FAL to LA. Consequently, H3PW12O40/SiO2 revealed to be a potential catalyst producing an similar to 51% LA yield under optimized reaction conditions. Moreover, the catalyst was found to be reusable for three catalytic cycles. This study paves the way to develop future biorefinery, particularly direct conversion of FUR to LA over a bifunctional catalyst with a liquid H-donor, in an environmentally benign manner and comply with the green chemistry principles.

Review on selective production of acetophenone from oxidation of ethylbenzene over heterogeneous catalysts in a decade - Nandanwar, Sachin U.; Rathod, Simmy; Bansal, Videsha; Bokade, Vijay V. (Catalysis Letters, 2021)
The consumption of acetophenone (AP) is increasing worldwide because of its applications in products such as alcohol, aldehydes, resins, esters, fragrances, and pharmaceuticals. AP is manufactured via several methods like decomposition of cumene hydroperoxide, Hock process, and Friedel-Crafts acylation reaction using homogeneous catalysts with solvent and oxidant. However, it causes several environmental problems that deteriorate the production of AP with these methods. Oxidation of ethylbenzene (EB) is one of the promising methods to synthesize AP in liquid and vapor phases reaction using heterogeneous catalysts, which plays a vital role for selective production of AP. In this review, numerous heterogeneous catalysts are discussed including transition metal nanoparticles, transition metal complexes, and metal free catalysts (carbon nanotubes) used in last 10 years for oxidation of EB. Additionally, catalyst activity along with reaction parameters and its effect, mechanisms, and kinetics study are summarized in this article. The future scope of this reaction is also highlighted. Moreover, this work identifies best catalysts for bulk production of AP with high yield to satisfy global requirement.
Keywords: acetophenone; ethylbenzene; Heterogeneous catalysts; Oxidation reaction; reaction mechanisms